Comparison of clinical, laboratory, radiographic, and scintigraphic findings in erosive and nonerosive hand osteoarthritis. Results of a two-year study - Olejárová, M; Kupka, K; Pavelka, K; Gatterová, J; Stolfa, J (Joint bone spine, 2000)
OBJECTIVES: The primary objective was to compare the clinical, radiologic, laboratory, and scintigraphic features in 28 patients with erosive hand osteoarthritis and in 24 with non-erosive hand osteoarthritis. Other objectives were to evaluate clinical, radiographic, and scintigraphic progression in the two groups over a two-year period and to estimate the value of bone scintigraphy for predicting clinical and radiographic progression. METHOD: Prospective two-year study of 52 patients with hand osteoarthritis, of whom 28 had at least three subchondral erosions and 24 patients had no erosions. RESULTS: The group with erosive disease had higher serum immunoglobulin G levels (14.53 +/- 3.79 mg/L vs. 12.03 +/- 4.01 mg/L; P < 0.05) and a higher radiographic index (91.81 +/- 3.67 vs. 25.88 +/- 12.81; P < 0.001), whereas the group with non-erosive disease had a higher rate of paresthesia (66.7% vs. 39.3%; P < 0.05) and higher values for the erythrocyte sedimentation rate (25.21 +/- 20.86 vs. 13.21 +/- 12.85; P < 0.05) and serum C-reactive protein level (8.82 +/- 6.08 vs. 3.25 +/- 6.92; P < 0.01). None of the other study parameters showed any significant differences, and both age and sex distribution were also similar in the two groups. At completion of the two-year follow-up, no changes versus baseline were found in any of the study parameters in the overall study population or in either of the two groups. The baseline scintigraphic index was significantly correlated with the radiographic index at baseline (r = 0.497; P < 0.01) and at study completion (r = 0.550; P < 0.001). Joints with a positive baseline scintigram were significantly more likely to show radiographic progression (21.09%, vs 6.68% in negative joints; P < 0.001) and joint tenderness exacerbation (21.22% vs. 13.73%; P < 0.001). CONCLUSION: These data suggest that bone scintigraphy may be useful for predicting clinical and radiographic progression of hand osteoarthritis with or without erosions.
Keywords: novorozenec; Infant, Newborn; Humans; Radiography; lidé středního věku; Disease Progression; radiografie; Female; Aged; senioři; lidé; osteoartróza; ženské pohlaví; Male; Middle Aged; Radionuclide Imaging; progrese nemoci; ruka; mužské pohlaví; radioisotopová scintigrafie; Hand; Osteoarthritis